Fishing in deep waters ; Hot cars ; Agnes of God - Lazaro, Cheche (The Probe Team, 1988)
Filipinos sailors are jailed in Malaysia for allegedly having fished illiegally in their territorial watrs. The rampant occurence of carnapping, its modus operandi and what happened to vehicles that are stolen ' The play by John Pielmeir, its philosophy and controversy of its theme.